Virtual classroom and digital culture in graduate students of a peruvian public university - Bustillos-Cotrado, Jose A. (2022)
The present study aims to determine the relationship between the virtual classroom and digital culture in research and higher education master's degree students at a Peruvian public university. Through a basic research, correlational level and non-experimental design of transectional type. With a total of 30 students selected through a non-probabilistic purposive sampling. The data were collected at two moments, using two questionnaires validated by judgment of 5 experts and with a reliability of cronbach's alpha coefficient of α=0.869 and α=0.849 respectively. The results show that for the virtual classroom variable, 36,67% always put it into practice, 53,33% sometimes and 10% never. On the other hand, for the digital culture variable; 23,33% evidenced that it is always being updated, 53,33%, sometimes and 23,33%, never. A positive average relationship was verified through Spearman's rank order correlation coefficient (Rho = 0.539; p = 0.002). It is concluded that the virtual classroom allows the development of a digital culture in graduate students; therefore, the training and development of digital competencies corresponds to all members of the academic community.